Chemoenzymatic Protocol for the Synthesis of Enantiopure β-Blocker (S)-Bisoprolol - Lucas Bocquin; Elisabeth Egholm Jacobsen (Catalysts, 2022)
The β-blocker (S)-bisoprolol hemifumarate has been synthesised in 96% enantiomeric excess with 19% total yield in a six-step synthesis. A transesterification reaction of the racemic chlorohydrin 1-chloro-3-(4-((2-isopropoxyethoxy)methyl)phenoxy)propan-2-ol catalysed by lipase B from Candida antarctica resulted in the R-chlorohydrin in high enantiomeric purity. Reaction of this building block with isopropylamine in methanol gave (S)-bisoprolol, and further reaction with fumaric acid gave (S)-bisoprolol fumarate in 96% ee. Specific rotation value confirmed the absolute configuration of the enantiopure drug.